A Patient with Typhoid Hepatitis - M Vitanata Arfijanto; Isty Rindryastuti (The Indonesian Society for Digestive Endoscopy, 2021)
Typhoid hepatitis is typhoid fever accompanied by symptoms of jaundice, hepatomegaly and abnormal liver function tests. The incidence varies between 0.4% -26% of typhoid fever patients. We report a case of a 34-year-old male, presented with fever, epistaxis, gastrointestinal symptoms, thrombocytopenia and elevated AST/ ALT, thus the patient was first diagnosed as dengue hemorrhagic fever grade II. On day 9th the signs and symptoms were persisted, Ig M and Ig G Dengue was negative. Then we evaluated the virus marker for hepatitis and blood culture. The results were negative for HBsAg, anti HCV and Ig M anti HAV, but Salmonella typhi detected on blood culture. The patient was treated with ceftriaxone 1000mg bid iv and get better then discharged from hospital.